A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
into
f(x) = (x+a)/b
g(x) = cx  d
So that they are inverses, meaning that the x and y values are reversed.
For example If a = 2 and b = 3 we would get
F(x) = (x + 2)/3 and g(x) = 3x  2
Part 2
To prove this you would switch the x and y values and solve for x . Remember that y is the same as f(x) and g(x).
Part 3
To evaluate g(f(x)) you substitute f(x) for x. In my example it would be 3((x+2)/3) 2. You then simplify it to find that f(f(x)) = x
Part 4
You make an input output chart for each function and you will see that the x and y values are just reversed.
Need help
anonymous
 one year ago
into f(x) = (x+a)/b g(x) = cx  d So that they are inverses, meaning that the x and y values are reversed. For example If a = 2 and b = 3 we would get F(x) = (x + 2)/3 and g(x) = 3x  2 Part 2 To prove this you would switch the x and y values and solve for x . Remember that y is the same as f(x) and g(x). Part 3 To evaluate g(f(x)) you substitute f(x) for x. In my example it would be 3((x+2)/3) 2. You then simplify it to find that f(f(x)) = x Part 4 You make an input output chart for each function and you will see that the x and y values are just reversed. Need help

This Question is Closed
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.